ANALISIS LINGUISTIK: EKSPLORASI NILAI ESTETIKA BAHASA DALAM SURAT AN-NAS AYAT 1-6 - Muhammad Luthfi Ardiansyah; Lista Dwi Narliyani; Lesa Rahmawati; Tasbihah, Tita (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2025)
The Qur'an is a holy book for Muslims that plays an important role in everyday life. The Qur'an has 114 surahs that have special qualities in them. An-nas is one of the surahs that has special values and deep meani ngs, each verse contains spiritual, protective, educational, and reflective values. The research findings show that Surah An-Nas has a high level of linguistic beauty through word choice, sentence structure, and the use of language styles such as repetition, parallelism, and connotation that strengthen the message of protection to Allah as God, King, and Protector of mankind. In Surah An-nas, it is emphasized that the characteristics of the language style of the Qur'an not only beautify the text, but also play a role in conveying meaning effectively and deeply, thus providing a new understanding of the verses. By using a linguistic and stylistic approach, this study contributes to deepening the understanding of the beauty and meaning of Surah An-Nas more comprehensively. This study aims to examine the aesthetic values contained in the language and provide an interpretation of Surah An-Nas verses 1-6 from a linguistic perspective. The approach used is qualitative with stylistic analysis, which examines the phonological, morphological and semantic aspects in the text of the Qur'an in order to reveal the beauty of the language and the meaning contained therein.